Sediment elemental composition (XRF) of sediment core GeoB19920-1, 30 kV run - Jens Weiser; Dierk Hebbeln (PANGAEA, 2025)
XRF Core Scanner data of sediment core GeoB19920-4 from Baffin BAy were collected every two centimetres downcore over an active area of 15 mm^2 with a downcore slit size of 10 mm using generator settings of 30 kV directly at the split core surface of the archive half with XRF Core Scanner II (AVAATECH Serial No. 2) at MARUM, Bremen.
In: Weiser, J; Hebbeln, D (2025): Sediment elemental composition (XRF) of sediment core GeoB19920-1 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.984308